Interaction effects between dynamic hybrid products and traditional deferred annuities in the German life insurance market - Nikolaj Moretti; Johannes Bartels (Financial Markets and Portfolio Management, 2021)
Dynamic hybrid products emerged in 2007 and are now well established in the German life insurance market. In this article, we study interaction effects between dynamic hybrid products and traditional deferred annuity contracts, that are sold by the same insurance company. The key question we investigate is whether the presence of dynamic hybrid products has a negative effect on the payout of traditional insurance products. We do so by using data drawn from a Monte Carlo simulation that is based on a model presented in this article. These data reveal that dynamic hybrid products reduce the payment to policyholders of traditional deferred annuities via the channel of surplus participation.
Keywords: G18; G22; 330; Life insurance; Guaranteed interest rates; Dynamic hybrid; Constant proportion portfolio insurance; Customer value; DTH product; Insurance regulation